Electrochemical Diagram of an Ultrathin Lithium Metal Anode in Pouch Cells. Issue 37 (5th August 2019) - Shi, Peng; Cheng, Xin‐Bing; Li, Tao; Zhang, Rui; Liu, He; Yan, Chong; Zhang, Xue‐Qiang; Huang, Jia‐Qi; Zhang, Qiang
Abstract: Lithium (Li) metal is regarded as a "Holy Grail" electrode for next‐generation high‐energy‐density batteries. However, the electrochemical behavior of the Li anode under a practical working state is poorly understood, leading to a gap in the design strategy and the aim of efficient Li anodes. The electrochemical diagram to reveal failure mechanisms of ultrathin Li in pouch cells is demonstrated. The working mode of the Li metal anode ranging from 1.0 mA cm −2 /1.0 mAh cm −2 (28.0 mA/28.0 mAh) to 10.0 mA cm −2 /10.0 mAh cm −2 (280.0 mA/280.0 mAh) is investigated and divided into three categories: polarization, transition, and short‐circuit zones. Powdering and the induced polarization are the main reasons for the failure of the Li electrode at small current density and capacity, while short‐circuit occurs with the damage of the separator leading to safety concerns being dominant at large current and capacity. The electrochemical diagram is attributed from the distinctive plating/stripping behaviors of Li metal, accompanied by dendrites thickening and/or lengthening, and heterogeneous distribution of dendrites. A clear understanding in the electrochemical diagram of ultrathin Li is the primary step to rationally design an effective Li electrode and render a Li metal battery with high energy density, long lifespan, and enhanced safety. Abstract : The failure mechanisms of ultrathin lithium in pouch cells can be divided into three categories: polarization, transition, and short‐circuit. A clear working pattern for ultrathin Li metal in pouch cells is established, which can potentially assist in designing a promising strategy for an advanced Li metal anodes.